The frequency of smoking, quitting smoking and the characteristics of smoking among nurses of a research and training hospital - Dilbaz, Nesrin; Apaydın, Leyla (Journal of Dependence, 2002)
Objective: In Turkey, the prevelance of cigarette smoking among general population and health professional is higher than the developed countries. This study is planned to determine the frequency of cigarette smoking, quitting and to evaluate the characteristics of smoking behavior qmong nurses that is the most crowded group of health professionals. Method: A semi-structured socio-demographic form which was formed of questions about smoking habits, cessation and smoking characteristics was applied to 250 nurses who are working in Ankara Numune Research and Training Hospital and who gave informed consent to participate the study. Results: The rate of smoking was 58.8 % and the rate of quitting was 14 % among the nurses who applied in this research. The rate of smoking was found higher in divorced/seperate/widow and single nurses whereas the quitting rate was higher in married nurses. In the study group the nurses who were 26-30 year-old and were working for 2-5 years had higher smoking rate than the others. We found that %45.1 of all smokers were smoking 11 -20 cigarettes per day. Smoking duration of cigarettes 42.3% was 6-10 years. 55% of the nurses was smoking their first cigarettes 60 minutes after they woke up, 71.4% was not smoking very much in the morning, 65.4% had their precious cigarette after the meals, 59.9% were having distress in smoking prohibited places, 27.5% were smoking when they were sick, 56.6% tried to quit but failed, 72.5% did not get angry when they criticized because of smoking, 90.2% did not neglect their responsibility because of smoking, 30.7% bought a pock of cigarette on the day that they decided to quit, 89% knew the harms of smoking and 5.5% were using another substance besides cigarette. The rate of agitation, loss of attention, irritability, the changes of mood during the cessation and the recovery of symptoms after starting smoking were 20.9%, 17%, 35.7%, 11.5% and 56% respectively. Conclusion: Smoking is an important health problem among nurses. Despite the lethal consequences of smoking more than half of the nurses still continue to smoke. To decrease the rote of smoking nurses must be trained about the harms of smoking and must be motivated to quit smoking.